2013
DOI: 10.1007/s00421-013-2738-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic activity-based therapy on bone mineral density and bone turnover in persons with spinal cord injury

Abstract: Purpose Osteoporosis is a severe complication of spinal cord injury (SCI). Many exercise modalities are used to slow bone loss, yet their efficacy is equivocal. This study examined the effect of activity-based therapy (ABT) targeting the lower extremities on bone health in individuals with SCI. Methods Thirteen men and women with SCI (age and injury duration = 29.7 ± 7.8 and 1.9 ± 2.7 years) underwent 6 months of ABT. At baseline and after 3 and 6 months of training, blood samples were obtained to assess bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 49 publications
2
27
0
2
Order By: Relevance
“…Paker et al observed a similar decrease in the CTX concentration after SCI as in the present study [32]. Astoroni et al found CTX and PINP concentrations among SCI males in the chronic phase to be lower compared to those of our findings [33]. Our findings suggest that increased bone remodelling activity and bone loss are still evident 1 year after injury in both motorincomplete and -complete SCI men.…”
Section: Discussionsupporting
confidence: 51%
“…Paker et al observed a similar decrease in the CTX concentration after SCI as in the present study [32]. Astoroni et al found CTX and PINP concentrations among SCI males in the chronic phase to be lower compared to those of our findings [33]. Our findings suggest that increased bone remodelling activity and bone loss are still evident 1 year after injury in both motorincomplete and -complete SCI men.…”
Section: Discussionsupporting
confidence: 51%
“…ABT consisting of multiple exercise modalities as listed above has been shown to enhance motor function in persons with SCI 14 and more recently slowed bone loss in this population. 15 Yet, its energy cost (5.1-8.6 ml/kg/ min as previously reported 16 ) is lower than that shown for arm ergometry 17 which may potentially reduce its ability to alter comorbidities associated with SCI. To our knowledge, the effects of multimodal ABT upon deleterious changes in body composition attendant with SCI are unknown.…”
mentioning
confidence: 78%
“…During the study, time performing active assistive exercises and passive gait training generally decreased while time performing resistance training and active gait training increased. ABT consisted of the following modalities as recently described 15 : 1.5-2.0 hours/week of active assistive exercise, 34 1.5-2.0 hours/week of upper/lower body and core resistance training, 1.5 hours/week of load bearing, 35 30 minutes/week of arm/cycle ergometry, 35 1.0-2.0 hours/week of gait training including assisted …”
Section: Completion Of Abtmentioning
confidence: 99%
“…The present study provides insight into the perceived benefits acquired by participating in an RCT comparing exercises to FES therapy and serves as a model for pinpointing domains of well-being that could be targeted for assessment in future SCI trials Astorino et al [23] Effect of chronic activity-based therapy on bone mineral density and bone turnover in persons with spinal cord injury Chronic activity-based therapy did not reverse bone loss typically observed soon after injury, yet reductions in BMD were less than the expected magnitude of decline in lower extremity BMD in persons with recent SCI Sadowsky et al [24] Lower extremity functional electrical stimulation cycling promotes physical and functional recovery in chronic spinal cord injury FES during cycling in chronic SCI may provide substantial physical integrity benefits, including enhanced neurological and functional performance, increased muscle size and force-generation potential, reduced spasticity, and improved quality of life Gorgey et al [25] Neuromuscular electrical stimulation attenuates high skeletal muscles atrophy but not trunk muscles after spinal cord injury NMES can delay the process of progressive skeletal muscle atrophy after chronic SCI However, the effects are localized to the trained high muscles and do not extend to the proximal trunk muscles Karimi et al [26] Robotic rehabilitation of spinal cord injury individual Although various types of orthotic systems have been developed for paraplegic subjects for walking and rehabilitation, there is not enough research in this regard. It is not easy to determine the therapeutic influence of robotic orthosis on the health status of paraplegic subjects There is a huge gap for a randomized clinical trial research to determine the effect of robotic system on the health status of the SCI subjects Karimi et al [27] Functional walking ability of paraplegic patients: comparison of functional electrical stimulation vs mechanical orthoses FES and hybrid orthoses offer considerable potential for restoring standing and walking abilities in persons with SCI.…”
Section: Ref Therapeutic Strategy Resultsmentioning
confidence: 99%